The evolution of patent mining: Applying bibliometrics analysis and keyword network analysis. (September 2016) - Madani, Farshad; Weber, Charles
Abstract: Text mining methods allow researchers to investigate technical documents (tech mining) and specifically explore patents for valuable information (patent mining. To the review literature and analyze the evolution of patent analysis and patent mining methods, bibliometrics analysis and keyword-based network analysis is applied on 143 papers extracted from the 'Web of science' database. Bibliometrics analysis was applied to determine top players researching in patent mining. Applying cluster analysis on the keyword network shows three main stages of patent analysis evolution. Also, it is discussed how patent mining is evolutionized in terms of information retrieval, pattern recognition and pattern analysis.